Antibacterial and Antifungal Activity of Functionalized Cotton Fabric with Nanocomposite Based on Silver Nanoparticles and Carboxymethyl Chitosan - Arenas-Chávez, Carlos Alberto (2022)
Cotton is the most widely used natural fiber for textiles; however, the capacity of cotton fibers to absorb large amounts of moisture, retain oxygen, and have a high specific surface area makes them more prone to microbial contamination, becoming an appropriate medium for the growth of bacteria and fungi. In recent years, the incorporation of silver nanoparticles in textile products has been widely used due to their broad-spectrum antibacterial activity and low toxicity towards mammalian cells. The aim of the current study is to continue the assessment of our developed nanocomposite and evaluate the antibacterial and antifungal activity of the nanocomposite based on silver nanoparticles and carboxymethyl chitosan (AgNPs-CMC) against Escherichia coli, Staphylococcus aureus, and Candida albicans, evaluated by the well diffusion method. The antibacterial activity against E. coli and S. aureus was also evaluated by the qualitative method of inhibition zone and the quantitative method of colony counting. Likewise, the antifungal activity of the functionalized fabric against Candida albicans and Aspergillus niger was determined by the inhibition zone method and the antifungal activity method GBT 24346-2009, respectively. The functionalized fabric showed 100% antibacterial activity against E. coli and S. aureus and good antifungal activity against C. albicans and A. niger. Our results indicate that the functionalized fabric could be used in garments for hospital use to reduce nosocomial infections.